Ontario Looking After Children 2022 Report - Miller, Meagan (Université d'Ottawa | University of Ottawa, 2023)
In July 2020, Ontario's Ministry of Children, Community and Social Services (MCCSS) released Ontario's Quality Standards Framework: A Resource Guide to Improve Quality of Care for Children and Young Persons in Licensed Residential Settings, a document that describes best practices for providing high-quality care in view of positive futures for young people. This framework is a compliment to the guiding principals of the Ontario Looking After Children (OnLAC) model, namely that good parenting leads to good outcomes. When substitute parenting (caregiving) is of high quality, young people are supported to develop and achieve goals, maintain connections with their communities and build healthy relationships, develop a strong sense of knowledge and pride in their unique identities, and foster resilience despite adversities they have experienced. Both the Quality Standards Framework and OnLAC seek to provide those caring for children and young people with a model for quality caregiving, and as such, they align well. The selected information presented in this report is the product of the OnLAC project's 22nd year of provincial data collection and aggregation via the Assessment and Action Record (AAR). The University of Ottawa OnLAC team has endeavoured to present information, measures, and variables that, when used in conjunction with contextual knowledge and other information sources, can help Ontario children's aid societies (Societies) to evaluate the quality of care provided to young people in care in Ontario in line with Ontario's Quality Standards Framework. This report is intended for use in three main areas: 1. Regular outcome monitoring, by comparing young people's developmental progress to intended goals 2. Evaluating and promoting continuous quality improvement and relevance of services 3. Providing policy-makers with accurate, up-to-date knowledge of system wide outcomes, fulfilling an accountability function The basic findings presented in this report must be reviewed and interpreted carefully by readers. Our attempt to confer this information as simply as possible has meant that we have had to be selective in what items and measures are presented and how. Societies are encouraged to undertake their own analysis and explore stratifications that are meaningful to local contexts, goals, and knowledge needs. If users have questions or comments about the findings described, or need assistance in interpreting their Society's own data, please contact Meagan Miller, OnLAC Research Associate, at mmiller@uottawa.ca. There is also a section of selected 'Further Reading" at the end of this report. Since 2000, the OnLAC project has been a partnership between the Centre for Research on Educational and Community Services (CRECS) at the University of Ottawa and the Ontario Association of Children's Aid Societies. We gratefully acknowledge the funding and support of OACAS and MCCSS. We also wish to thank the numerous child welfare workers, quality assurance staff, supervisors, managers, admin and executive personnel, caregivers, and especially, the young people in care who have contributed so much to the OnLAC project since the beginning.
Keywords: child welfare; ontario looking after children; child development